1993
DOI: 10.2172/10133543
|View full text |Cite
|
Sign up to set email alerts
|

The direct sampling ion trap mass spectrometer for the rapid analysis of volatile organic contaminants in groundwater samples

Abstract: Analytical results of volatile organic contaminant (VOC) concentrations in groundwater samples from A/M Area obtained using a direct sampling ion trap mass spectrometer (DSITMS) and a gas chromatograph (G_ with an electron capture detector (ECD) were comparable. Replicate water samples were collected at the Integrated Demonstration Site during four bii-weekly sampling periods and analyzed by both instruments. The calibration curves prepared for both the DSITMS and GC-ECD are essentially linear over the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The DSITMS differs from the other five technologies in that it does not have a gas chromatograph front end [8,9,24,25]. In the DSITMS, the GC sample introduction technique is replaced by a helium purge coupled to a modular, direct-sampling inlet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DSITMS differs from the other five technologies in that it does not have a gas chromatograph front end [8,9,24,25]. In the DSITMS, the GC sample introduction technique is replaced by a helium purge coupled to a modular, direct-sampling inlet.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported on the efficacy of field analytical methods to supplement or replace off-site methods for remedial characterization [1,2,8,[16][17][18][19][20][21][22][23][24][25][26][27]. Those studies focus primarily on the technical aspects of various instruments or procedures for performing VOC sample analysis in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…completed EPA Equivalency testing and is now an EPA approved method. A report has been completed which compares DSITMS results with baseline methods (Eddy-Dilek, et al 1993). 10 S Plus GC (Photovac, Inc.). The 10s Plus GC (approximately $24,OOO)-is an all inclusive field deployable GC with an isothermal oven and photo-ionization detector: The instrument has a built-in carrier gas reservoir, data analysis system, and rechargeable'battery.…”
Section: Long-term Field Evaluationsmentioning
confidence: 99%